Genome-wide association study and transcriptomic analysis reveal the crucial role of sting1 in resistance to visceral white-nodules disease in Larimichthys polyactis - Zhu, Jiajie; Liu, Feng; Ye, Ting; Li, Qian; Liu, Haowen; Liu, Sifang; Zhang, Tianle; Guo, Dandan; Zhu, Junquan; Lou, Bao (Frontiers in Immunology, 2025)
IntroductionLarimichthys polyactis is a promising marine fishery species, but visceral white-nodules disease (VWND) caused by Pseudomonas plecoglossicida causes significant losses. However, genetic resistance mechanisms to VWND remain elusive in this species.MethodsThis study combined genome-wide association study (GWAS) and transcriptome analysis to unravel resistance loci and transcriptional regulation in L. polyactis.ResultsAs a result, GWAS on 946 infected fish genotyped by 100 K lipid chips identified 22 suggestive significantly associated single-nucleotide polymorphisms (SNPs), annotated 60 candidate genes, where DNA-sensing pathway were enriched. RNA-seq on liver tissues of resistant, sensitive, and control groups found immune-related pathways enriched in the comparisons of RL vs CL and RL vs SL, and autophagy-related pathways enriched in the comparisons of SL vs CL and RL vs SL. Then, the integration of GWAS and transcriptome analysis identified seven key genes associated with resistance to VWND. Among the genes, the expression levels of mRNA for genes related to the cyclic GMP-AMP synthase-stimulator of interferon genes (STING) signaling pathway, as well as the protein levels of STING1, were significantly upregulated in RL. Collectively, integrating KEGG pathway analysis, gene and protein expression analysis revealed that the importance of STING1 for VWND resistance.DiscussionThese findings deepen the available knowledge on molecular mechanisms of host genetic resistance to VWND and provide an important foundation for the selection and breeding of VWND-resistant L. polyactis.